Impact of career success on organizational performance: A study of health care sector - Memoona Naseer; Atif Mahmood; Sara Kanwal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Management and organizational studies consider career success and organizational performance as imperative constructs. However, there has been dearth of literature with respect to its practice in healthcare field. Purpose of current study is to determine impact of career success on organizational performance of public health care hospitals, and to investigate possible dimensions of included variables. Preliminary snooping incorporated focused group and semi-structured interviews of medical practitioners who are currently working in the public hospitals in Lahore. In addition a questionnaire was distributed through convenience sampling technique. Out of total 300 distributed questionnaires, 200 were received back. EFA reveals four dimensions of career success and three dimensions of organizational performance. SEM results prove that career success of medical practitioners is important for improving performance of public hospitals in Lahore, Pakistan. This research is helpful for policy making and strategic development in health care field. However, the findings are limited to the local setting of Pakistan.
Keywords: 330; career success; organizational performance; medical practitioners; public sector hospitals; young doctors association (YDA)